Ofiary przebłagalne: od rytuału do teologii (Kpł 4,1-35; Lb 15,22-31) - Rosik, Mariusz (Verbum Vitae, 2005)
Sacrifices were the principal act in Israel’s cult. The article treats about expiatory sacrifices in ancient lsrael. The purpose ofthese sacrifices is to re-establish the covenant with God. Autbor describes the circumstances when expiatory sacrifices should be offered and then explains difference between the sacrifice for sin (hattath) and the sacrifice of reparation (asham). He also gives the scheme of the ritual of expiatory sacrifices. Theological meaning o f these sacrifices is shortly presented in the conclusion.